Cheilitis Glandularis of Both Lips: Successful Treatment with a Combination of an Intralesional Steroid Injection and Tacrolimus Ointment - Norberto Sugaya; Dante Migliari (Hindawi Limited, 2018)
Cheilitis glandularis (CG) is an inflammatory condition of unknown cause that predominantly affects the minor salivary glands of the lips. Although a diagnosis of CG is not difficult, its treatment is a challenge. This article highlights the clinical presentation of the disease together with a case of successful management of this disease using a combination of a steroid injection followed by a topical immunosuppressor.